2021
DOI: 10.1007/s12070-021-02546-4
|View full text |Cite
|
Sign up to set email alerts
|

Tele Otology in India: Last 10 Years—A Scopic Review

Abstract: Hearing loss is the commonest sensory deficit among humans, affecting 466 million people worldwide. Early detection is the key to hearing rehabilitation, as speech and language develops early in the childhood. Scarcity of human resources and infrastructure in developing countries like India leads to difficulty in implementation of hearing screening programmes. Tele otology is very fruitful methodology in providing health care facility from distant site to the doorsteps of needy individuals. The action initiate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Improvement in patient outcome (n=16)(7478,81,82,8587,89,9194,96), improvement in knowledge of HCP (n=3)(76,85,89), and improvement in work performance (n=3)(76,85,92) were associated with the use of telemedicine. It also helped in reducing travel (n=4)(78,91,92,94) and when used for remote diagnosis, telemedicine showed no significant diagnostic difference when compared with conventional diagnostic modalities (n=3)(79,88,92). The other impacts are mentioned in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Improvement in patient outcome (n=16)(7478,81,82,8587,89,9194,96), improvement in knowledge of HCP (n=3)(76,85,89), and improvement in work performance (n=3)(76,85,92) were associated with the use of telemedicine. It also helped in reducing travel (n=4)(78,91,92,94) and when used for remote diagnosis, telemedicine showed no significant diagnostic difference when compared with conventional diagnostic modalities (n=3)(79,88,92). The other impacts are mentioned in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-one studies (84%) were quantitative (7277,7982,8489,91,9396), 2 (8%) were qualitative (78,83), 1 (4%) followed mixed methodology (90) and 1 (4%) was a review study. (92) No study on the use of telemedicine by human resources for health (HRH) was published before 2011. A majority (64%)(7478,82,8487,89,9193,95,96) of the studies were published after 2017 with the maximum (n=5, 20%)(75,77,84,86,91) number of studies being published in 2020.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic and scoping reviews have reported studies in tele-audiology [6][7][8][9][10] . The primary goal of these reviews has been to analyse evidence regarding telepractice applications in terms of treatments offered for ear and hearing disorders, as well as details about patient-site facilitators.…”
Section: Introductionmentioning
confidence: 99%